PENGARUH SIARAN PIALA DUNIA TERHADAP KEPEMILIKAN ATRIBUT SEPAK BOLA MAHASISWA KOMUNIKASI UIN SUSKA RIAU - AGUS ANJAR AGUS ANJAR; Gomal Juni Yanris (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2021)
The purpose of this study was to determine the 2006 world football broadcast broadcast by the private television station SCTV to the ownership of the soccer club attributes of students majoring in Communication Science, UIN SUSKA Riau. The rapid development in the field of communication and information, has placed the mass media in an important position, some television media which are very effective means of providing various information to the public such as the 2006 World Cup broadcast broadcast in Germany. The problem is that these publications have implications for the communication soccer club attributes. Then the method used to get answers from the problem formulation using descriptive qualitative. As for the research subjects, students majoring in Communication Studies were incorporated into the Communication Studies football club, while the object of this research was the 2006 World Cup broadcast broadcast by SCTV. Data collection techniques in this study used questionnaires, interviews and observations which were then analyzed by using the formula P = f / n = 100. While the results of the data analysis obtained a quantitative average of 70.72%, while that was a factor causing soccer clubs communication department majoring in watching world cup soccer broadcasts is relatively high, obtained quantitative data of 79.66% this is due to hobby factors, social factors, and economic factors.